Effect of Thermal Processing on Elimination of Antinutritional Factors in Irvingia smithii Almond - V.G. Gindo Mbaya; P.E. Sumbu Zola; E. Kimbemuken Thasur; D. Mayele Kipoy (Britain International of Exact Sciences (BIoEx) Journal, 2023)
The objective of this work is to identify and eliminate antinutritional factors in the fruit kernel of Irvingia smithii (wild mango tree) from the KISANTU botanical garden (DRC) by thermal effect at different temperatures (T1: sun drying, T2: roasting in an oven at 130° C for 30 minutes, T3: boiling for 45 minutes) as a function of time. It appears from the results of our analyzes that the fruit kernels of Irvingia smithii contain antinutritional factors in low proportions: phytates (536.34mg/100g), oxalates (14.84mg/100g), nitrates (12.71mg/100g, 8), and nitrites (50.15mg/100g,). Saponins were not found in these almonds. Treatment of almonds by boiling for 45 minutes (T2 treatment) proved to be the best eliminator of antinutritional factors (60%) followed by treatment of almonds by roasting (T3) (43%), probably by the dissolution of antinutritional factors in medium aqueous (hydrolysis) and their evaporation by boiling which takes place during cooking. Wild mango (Irvingia smithii) levels of antinutrients are low enough to cause poisoning in their consumers; they have not yet been detected in human tissue or the urine of their consumers. We recommend that the roasting of the almond is done before cooking which is done by boiling, a process which will eliminate almost all the antinutritional factors.